Surgical Management of Dystocia due to Schistosomus Reflexus in a Non-Descript Goat - Sarath, Thulasiraman; Pavithra, Rajesh; Manokaran, Sakthivelu; Rajkumar, Ramasamy; Thangamani, Annadurai (The Indian Journal of Animal Reproduction, 2025)
A pluriparous full term pregnant non-descript goat was presented with a history of showing parturition signs for the past 12 hours. Fetal delivery was attempted by a local paravet but failed to relieve the dystocia. During admission, the animal was having occasional straining with exposed abdominal viscera of the fetus through the birth canal. The general clinical parameters were within the normal range. Vaginal examination revealed that the fetal mal-disposition with abnormal shape which was suggestive of a fetal monster. The attempted mutation and forced traction were unsuccessful, necessitating a caesarean section. During the procedure, a true Schistosomus reflexus fetus was delivered. The doe was treated with parenteral antibiotics, anti-inflammatory drugs, antihistamines, ecbolics and supportive therapy for five days, leading to an uneventful recovery without complications.